PENGGUNAAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN PENGETAHUAN DASAR TEKNIK MESIN DI KELAS X SMK NEGERI 5 PADANG - Fikri Fadillah; Refdinal Refdinal; Delima Yanti Sari; Fiki Efendi (Jurnal Vokasi Mekanika (VoMek), 2024)
Social media is widely used in education for various learning activities, such as searching for educational materials, using it as a tool, giving assignments, participating in discussion forums, and many more. Optimizing learning outcomes is the goal of using social media in the classroom. Online communities, bloggers, social media, wikis, forums and virtual worlds are examples of social media platforms where users can interact, share and create content easily. This study aims to introduce social media as a teaching aid in the subject of basic knowledge of mechanical engineering (PDTM), Department of Machining Engineering Class X, State Vocational High School 5 Padang. A total of 32 class x students Department of Mechanical Engineering participated in the study January-June 2023/2024 school year. The results showed an increase from pre test to post test. In the pre-test value obtained a value of 74.422 and the post-test learning outcomes were 79.79, this. This proves that, there is a difference between learning outcomes that use audio visual media and do not use audio visual media at State Vocational High School 5 Padang.